Essential Principles of Preoperative Assessment in Internal Medicine: A Case-Based Teaching Session - James C. Hudspeth; Michael Schwartz; Patrick Fleming; Thomas Ostrander; Mara Eyllon (Association of American Medical Colleges, 2021)
Introduction Preoperative assessment is a core competency for internal medicine residents, but one with limited educational resources available presently. Ideally, residencies would provide an introduction to this topic prior to their residents performing preoperative assessments in clinic or during internal medicine consultation rotations. Methods We developed a 120-minute case-based teaching session on preoperative assessment for PGY 2 residents where they reviewed a series of cases, applied preoperative risk calculators, and made recommendations on medication management using the same online tools they employ while working clinically. Interspersed lecture sections reviewed guiding principles, detailed key trials, and explored nuances of the topic. We performed pre- and posttests of knowledge and also obtained learner feedback. Results Thirty-three out of 40 participants completed the pre- and posttests. The session was rated highly (M = 4.0 out of 5) and was viewed as preferable to a lecture-based approach (M = 4.4 out of 5); mean participant knowledge improved from 11.7 to 17.5 (p < .001) out of 22 points possible. The most consistently offered feedback was to give more time for the session than the 120 minutes allotted. Discussion A teaching session mixing lecture with review of composite cases and application of preoperative assessment tools with immediate feedback improved knowledge and was viewed as enjoyable and preferable to lecture alone by participants. We recommend providing more time for the teaching by increasing the session length from 120 minutes to 140 minutes.